Premature Attraction of Pollinators to Inaccessible Figs of Ficus altissima: A Search for Ecological and Evolutionary Consequences - Zhang, Yuan; Peng, Yan-Qiong; Compton, Stephen G.; Yang, Da-Rong (PloS one, 2014)
Adult life spans of only one or two days characterise life cycles of the fig wasps (Agaonidae) that pollinate fig trees (Ficus spp., Moraceae). Selection is expected to favour traits that maximise the value of the timing of encounters between such mutualistic partners, and fig wasps are usually only attracted to their hosts by species- and developmental-stage specific volatiles released from figs at the time when they are ready to be entered, oviposited in and pollinated. We found that Ficus altissima is exceptional, because it has persistent tight-fitting bud covers that prevent its Eupristina altissima pollinator (and a second species of 'cheater' agaonid) from entering its figs for several days after they start to be attracted. We examined the consequences of delayed entry for the figs and fig wasps and tested whether delayed entry has been selected to increase adult longevity. We found that older pollinators produced fewer and smaller offspring, but seed production was more efficient. Pollinator offspring ratios also varied depending on the age of figs they entered. The two agaonids from F. altissima lived slightly longer than six congeners associated with typical figs, but this was explainable by their larger body sizes. Delayed entry generates reproductive costs, especially for the pollinator. This opens an interesting perspective on the coevolution of figs and their pollinators and on the nature of mutualistic interactions in general.